Differential mnemonic consistency differs between experienced and fabricated incidents. Issue 10 (25th November 2020) - Lange, Thorsten; Bell, Raoul; Buchner, Axel
ABSTRACT: The degree of consistency of reports across several interviews is often taken as indicating whether a report is experience-based or fabricated. However, due to forgetting some aspects of mnemonic reports will be inconsistent across interviews independent of whether a report is experience-based or fabricated. The concept of differential mnemonic consistency implies that certain elements of experienced incidents such as core activities are remembered relatively well whereas other elements of experienced incidents such as peripheral activities are more easily forgotten. This difference in mnemonic consistency has been claimed to be higher for experienced-based than for fabricated reports. We tested this prediction. Participants experienced or fabricated an 'examination' in which their blood pressure, body height, and body weight were measured. N = 326 participants reported as many details as possible immediately and four weeks after the incident. Mnemonic consistency between reports was indeed higher for elements with high than for elements with low expected mnemonic consistency. Most importantly, this difference in mnemonic consistency was larger in experience-based than in fabricated reports. The results suggest that differential mnemonic consistency could serve as a supplemental criterion for distinguishing between experience-based and fabricated reports but further research is necessary to determine its usefulness in forensic practice.